Pelaksanaan Kegiatan Praktikum Sederhana dalam Pembelajaran IPAS (Studi Kasus pada Tiga SD Banda Aceh) - Azizah, Nada; Oviana, Wati; Jannah, Misbahul; Herawati, Herawati (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2026)
The Independent Curriculum calls for students to actively participate in science classes through simple practicum exercises, However, the problem is that not all schools carry out simple practicum exercises in science learning. The purpose of this research is to outline the preparation, execution, and challenges of basic hands-on scientific learning activities in three Banda Aceh elementary schools. The study employed a case study design and a qualitative methodology. Teacher interviews, observation, and document analysis were used to gather data, which was then descriptively evaluated. The subjects of this study took three teachers from three different schools, namely SD Negeri 35 Banda Aceh, SD Negeri 54 Banda Aceh and SD Negeri 46 Banda Aceh. The data analysis technique used was data triangulation.The findings demonstrated how well-organized and in line with learning objectives the practical preparation was. Students were allowed to actively participate in the actual implementation and acquire science process skills. Time management and the classroom were the main areas of difficulty. It has been demonstrated that straightforward practical exercises improve students' comprehension of scientific ideas in a more tangible and significant way. Keywords: Simple Practicum, IPAS, Merdeka Curriculum, Elementary School